Incidence of heart failure in gerontological institutions (Jóvenes en la Ciencia, 2024)
Heart failure causes a negative impact on the life of the elderly, both in physical function and psychosocial function, worsening the deterioration with the increase in functional class. Objective: To identify the prevalence of heart failure in public geriatric institutions in Irapuato, Guanajuato. The NYHA (New York Heart Association) scale was applied. The sample consisted of 17 geriatric users of the Irapuato Gerontological Center and 26 of the "La Paz" Home, with an age range of 50 to 90 years of both sexes. Based on the New York Heart Association (NYHA) scale, compared to the manifestations of physical activity to be performed, it was demonstrated that the incidence of moderate heart failure prevailed with 47% of the total sample (Class III), presented marked limitation to the exercise. Symptoms appear with minor physical activities (such as walking). They disappear with rest, while users who are in Class I, without any physical limitation, without excessive fatigue after performing ordinary activities are minority with 7%. These results suggest that there are beginnings of heart failure in the institutions of La Paz Nursing Home and Irapuato Gerontological Center, with a significant burden of morbidity.